Sistem Pendukung Keputusan Penentuan Ekstrakurikuler Berdasarkan Minat dan Bakat Menggunakan Metode SMART Berbasis Website (Studi Kasus : SMA PGRI 1 Bandung) - Dani Pradana Kartaputra; Megga Nurdianti; Faiqunisa Faiqunisa (LPPM STMIK Bandung, 2024)
The rapid development of technology has driven many companies and institutions to use computers to solve various problems. One such application of technology is the decision support system (DSS) for determining students' talents and interests in extracurricular activities. Extracurricular activities are an essential part of the learning process, serving to channel students' talents and interests, as well as fostering their potential development. SMA PGRI 1 Bandung aims to develop students' potential not only through academic activities but also through non-academic activities, including extracurriculars. Currently, the process of selecting extracurricular activities at SMA PGRI 1 Bandung is conducted manually by filling out registration forms distributed by the student affairs department. This method is considered ineffective due to various issues such as lost forms, uneven distribution of forms, and students choosing extracurricular activities that do not match their character. To address these problems, a webbased Decision Support System (DSS) using the Simple Multi Attribute Rating Technique (SMART) method is needed. The SMART method uses criteria weighting to evaluate alternatives and determine the best choice. This research applies the SMART method into a web-based DSS to assist in selecting extracurricular activities for students. By involving several criteria in the selection process that are more personal to the students, the results obtained will be more aligned with the students' desires, thus reducing errors in selecting extracurricular activities.